The Connection Between the Quality of Life and Sustainable Ecological Development - Gazzola, Patrizia; Querci, Elena (European Scientific Journal, ESJ, 2017)
The research aims to analyze the evolution of the concept of sustainable ecological development and the central rule of the government policy for the improvement of the quality of life. The paper, using the model of five capitals, explains how the sustainable ecological development can help to improve the quality of life of citizens. A minimum necessary condition for sustainable ecological development is the maintenance of the total natural capital stock at or above the current level. This work explores the link between natural capital and sustainability from a government policy perspective and it examines how sustainable ecological development must be integrated within public sector organization’s planning. The research considers that the goal of sustainable ecological development is to use the natural resources wisely in the short-term so that these resources are available in the long-term. Ecological sustainability relies on the fact that humans can exhaust the natural resources, leaving nothing but polluted water and infertile soil for future generations. Ecological sustainability is the belief that all humans must use resources wisely and efficiently so that these resources never become exhausted or over polluted.